Excitation of the Auditory System as a Result of Non-invasive Extra-Cochlear Stimulation in Normal Subjects and Tinnitus Patients - Mielczarek, Marzena; Norena, Arnaud; Schlee, Winfried; Olszewski, Jurek (Frontiers in Neuroscience, 2018)
The first experiments with ES at the Medical University of Lodz dates back to the 80’s. At first invasive transtympanic promontory positive DC stimulations were used. Next we’ve developed a non-invasive approach - hydrotransmissive stimulations through external acoustic canal with the use of positive DC. The first aim of our study was to investigate further the mechanisms of non-invasive extra-cochlear electric stimulation on normal hearing and no tinnitus subjects. The second - was to assess the effects of non-invasive extra-cochlear electric stimulation on tinnitus in tinnitus patients. The material was composed of two groups: tinnitus group - 49 patients suffering from tinnitus, and healthy students group - 21 healthy individuals. ES was performed with the use of a custom-made apparatus. The active, silver probe – was immersed inside saline filling external ear canal. The passive electrode was placed on the forehead. Positive and next negative DC stimulation was provided with the use following frequencies: 0.25, 1, 2, 3, 4, 5, 6, 7, 8 kHz. We checked for the presence of the auditory precept (AP) and, if AP was present, the minimum current amplitude necessary to produce AP was measured. Results. In our research both positive and negative polarities were efficient to evoke an auditory perception (AP) in the study participants. This effect, however, was more pronounced for positive polarity in no tinnitus and normal hearing individuals (healthy students group). In tinnitus group current intensity needed to evoke an AP was higher than in healthy students group. However, comparing normal hearing vs hearing loss patients within tinnitus group, again, we didn’t observe the relationship between hearing threshold and current intensity evoking AP. Afterwards, we analysed the effect of multi-frequency ES on tinnitus. It appeared to be effective in 75% of tinnitus ears (with a high score of disappearance – 22%). Our study proved that extracochlear ES with positive and negative current was efficient to stimulate the auditory system. Auditory nerve appeared to be the most probable place of AP generation. Stimulating tinnitus ears with two polarities we obtained a higher ratio of improvement (75%) comparing to e.g. positive stimulations.